Analisis Karakter Kedisiplinan Peserta Didik TK Islam Roudlotus Salamah dalam Pengimplementasian Kurikulum Merdeka - Imanda, Frischa Amalia; Baihaqi, Ahmad Rizal; Zahrah, Naurah Salsabila Az (Darul Yasin Al Sys, 2023)
Character education has been initiated by the government and has become mainstream at various levels of education. In the curriculum scheme, the implementation of the project to strengthen the profile of Pancasila students is contained in the formulation of Minister of Education and Culture Decree No.56/M/2022 concerning Guidelines for Implementing Curriculum in the Context of Learning Recovery which states that the Curriculum Structure at the PAUD and Primary and Secondary Education levels consists of intracurricular learning activities and projects strengthening the profile of Pancasila students. This research aims to: 1) Define the character of discipline. 2) To find out the application of the independent learning curriculum to the disciplined character of students. 3) To determine the supporting and inhibiting factors in improving the disciplined character of students through the independent learning policy. This research uses a type of descriptive research with a qualitative approach, in accordance with the aim of this research, namely to analyze the Disciplinary Character of Roudlotus Salamah Islamic Kindergarten Students in Gresik Regency in Implementing the Merdeka Curriculum. Qualitative methods attempt to understand, explain and interpret the meaning of an interaction event involving human behavior in a particular situation according to the researcher's own perspective. The concept of Independent Learning is part of returning the national education system to the supremacy of law, in particular ensuring academic independence and instilling basic skills in curriculum teaching and is closely related to its influence in disciplinary character education when used as a provision for the importance of developing discipline and encouraging the development of character values.